1982
DOI: 10.1159/000241515
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preweaning Undernutrition upon the Sexual Development of Male Mice

Abstract: Sexual maturation was evaluated in male mice subjected to preweaning undernutrition by separating pups from their mothers. Underfed and normally fed males were sacrificed at 20, 30, 40, 50 and 60 days of age. From 20 to 60 days, body and organ weights (testes, seminal vesicle) were lower in underfed males. Plasma testosterone levels were lowered in undernourished males at 20 and 30 days of age, and thereafter they were not significantly different from controls. First fertile matings, which occurred between 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The sexual maturation in male mice was reported to be 36-46 days (mean age: 40.6 ± 0.6) [37]. Therefore, the male offspring were sacrificed at PND 45 for measuring the various parameters indicating testis development.…”
Section: Discussionmentioning
confidence: 99%
“…The sexual maturation in male mice was reported to be 36-46 days (mean age: 40.6 ± 0.6) [37]. Therefore, the male offspring were sacrificed at PND 45 for measuring the various parameters indicating testis development.…”
Section: Discussionmentioning
confidence: 99%
“…For example in men with idiopathic hypogonadotropic hypogonadism (IHH), a congenital hypothalamic inability to transcribe and secrete GnRH, patients who are exposed to endogenous GnRH during adolescence are more responsive to postadolescent GnRH treatment (Spratt and Crowley, 1988). Testicular function has also been shown to be permanently altered by preadolescent undernutrition in mice (Jean-Faucher et al, 1982). Adolescent priming may also underlie population variation in ovarian function (Ellison, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Ellison (1997) proposed that environmental conditions affecting energy availability during human female puberty may underlie variation in adult ovarian function. While the role of hormonal priming in male adolescents remains to be fully elucidated, variation in HPT function and pubertal development in association with energy availability has been documented in rodents, nonhuman primates, and humans (Cameron, 1991;Dubey et al, 1986;Jean-Faucher et al, 1982;Kulin, 1996;Kulin et al, 1982Kulin et al, , 1984. Kulin et al (1984) reported that undernourished Kenyan male adolescents exhibited delayed pubertal LH and FSH increases compared to well-fed controls living in affluent neighborhoods of Nairobi.…”
Section: Reproductive Endocrinologymentioning
confidence: 99%